Marcas da oralidade em textos de discentes em instituições de ensino público de Fortaleza-CE - Uchoa, Francisco Geovane Araujo (2022)
The uses of language, as well as its teaching and learning at school, deserve a significant look by scholars and professionals who work in education, and in this sense, it is that the present research has its relevance, as it proposes to study the marks of orality in students’ writing, which begins with the investigative question: is there a presence of orality marks in students’ texts in municipal public education institutions in Fortaleza/CE? From this concern, we aim to show that these marks, identified as characteristics of oral speech, can be found in the written speech of students. Therefore, we structured the theoretical foundation based on authors such as Marcuschi (1989, 1992, 1995, 1998, 2001); Pontes (1988); Ramos (1999); Rector & Trinta (1986, 1995); Urbano (1993); Antunes (1994); Bagno (2000); Barros (2000); Cagliari (1992); Castilho ( 1989, 1990, 2000); Fávero (2002); Koch (1995, 1997, 2009, 2010, 2015); Lyons (1981). The present research of basic nature fits as quali-quantitative, descriptive and field. Is used essays and questionnaires as instruments. The essays were concrete sources of the study carried out by the researcher on the marks of orality in the students’ texts, and the questionnaires were a source of reflection on the understanding of the final actors involved in the classroom with the teaching-learning of the portuguese language, which at school is directed more specifically to writing and there are understandings that cannot, in any way, discredit and disregard the oral modalities. That are in use in different segments of society, at all levels. The study also takes into account the issue of linguistics prejudice, which reinforces the idea that linguistic variations are inferior to the standard norm. Based on a sociolinguistic view, it is understood that it is up to the school, therefore, to teach normative grammar, but with the responsibility of also adding as an educational focus, the importance of studying oral modalities within a social vision without prejudice and welcoming, so that the student can appropriate the knowledge of the language, and be able to use it in the various possible ways within their needs for social uses.